Respuesta :
[tex]x = \frac{1}{2}[/tex] and [tex]y = - \frac{3}{2} [/tex]
Step-by-step explanation:
[tex] \frac{2x}{x + y} = \frac{3}{2} [/tex]
[tex] = > \frac{x + y}{xy} = \frac{4}{3} [/tex]
[tex] = > \frac{1}{x} + \frac{1}{y} = \frac{4}{3} [/tex]---- Eq. 1
Then,
[tex] \frac{xy}{2x - y} = - \frac{3}{10} [/tex]
[tex] = > \frac{2x - y}{xy} = - \frac{10}{3} [/tex]
[tex] = > - \frac{1}{x} + \frac{2}{y} = - \frac{10}{3} [/tex]-- Eq. 2
Let
[tex] \frac{1}{x} = u[/tex]and
[tex] \frac{1}{y} = v[/tex].
Then, from Eq. 1 & 2, we get:
[tex]u + v = \frac{4}{3}[/tex] and
[tex] - u + 2v = - \frac{10}{3} [/tex]
[tex] = > 3u + 3v = 4[/tex]and
[tex] - 3u + 6v= - 10[/tex]
By adding, we get,
[tex]9v = - 6[/tex]
[tex] = > v = \frac{ - 6}{9} [/tex]
[tex] = > v = - \frac{2}{3} [/tex]
Substituting "y" got above in Eq.1, we get,
[tex] \frac{1}{x} - \frac{2}{3} = \frac{4}{3} [/tex]
[tex] = > \frac{1}{x} = \frac{6}{3} = 2[/tex]
[tex] = > x = 2[/tex]
Hence,
[tex]x = \frac{1}{2} [/tex]
[tex] = > y = - \frac{3}{2} [/tex]
The value of x in the given expression is ²/₃ and y is -6.
Simplification of the linear equation
The given linear equation can be simplified by equating the variables to the equivalent values as shown below;
[tex]\frac{2xy}{x + y} = \frac{3}{2} \\\\4xy = 3x + 3y\ \ ---(1) \\\\[/tex]
Equation (2) is obtained as follows;
[tex]\frac{xy}{2x - y} = \frac{-3}{10} \\\\10xy = -6x + 3y \ ---(2)[/tex]
Multiple equation (1) by 2
8xy = 6x + 6y
Add equation (1) and (2) together
8xy = 6x + 6y
10xy = -6x + 6y
---------------------------
18xy = 12y
divide both sides by "y"
18x = 12
x = 12/18
x = ²/₃
Solve for y
8y x (²/₃) = 6(²/₃) + 6y
16y/3 = 12/3 + 6y
Multiply through by 3
16y = 12 + 18y
-2y = 12
y = -6
Learn more about linear algebra here: https://brainly.com/question/14323743